PLANKTON DISTRIBUTION IN CONTROLLED WATER OF MILKFISH LARVA CULTURE SYSTEM - Afifah Nasukha; Titiek Aslianti (BERITA BIOLOGI, 2019)
The selection of planktons as live feed for milkfish larvae is a vital tool to meet the natural character as herbivorous species and to fulfill the needs for nutritious food for fish larval growth and survival. Phytoplankton Nannochloropsis sp. and zooplankton rotifer (Brachionus sp.) were two-selected plankton used as the main food source for the milkfish larvae. We performed this study in two times larval culture batch with four observations of tanks as replication. The results showed that we nourished both targeted planktons as larval food, regarding the positive impacts on larval growth (12±1,37 mm of total length, 7±4.89 mg of body weight) and a high survival rate (65.93–77.70%) achieved at the end of the culture period. Plankton diversity analysis presented that Class of rotifer (Monogononta) and Nannochloropsis sp. (Eustigmatophyceae) were both counted as the most dominant plankton group found in the rearing media, showing a decent sign of food supply for fish in rearing water column. The total number of planktons was high and had the tendency to follow the concentration of selected planktons over the culture period in the controlled water.